Multisystemic Adverse Reactions to Amlodipine Mimicking Vasculitis - Chakraborty, Sudipto; Sengupta, Debroop; Rahaman, Mohidur; Dey, Pradip; Moitra, Saibal; Sen, Dhiman (Brazilian Journal of Case Reports, 2025)
A 52-year-old lady, with hypothyroidism and hypertension for the last 2 months, presented with complaints of low-grade fever, gum hypertrophy, abdominal pain, palpable purpura, bilateral knee joint swelling, and bruising of both lower legs for the last 1 month. She had a significant fall in haemoglobin, a high Reticulocyte count, increased bilirubin level, and persistently high potassium with a positive Direct Coombs test. After the initial assessment, she was clinically diagnosed with an Adult-onset Henoch-Schonlein Purpura. She underwent skin biopsy, suggestive of Drug Rash- Amlodipine being implicated as the drug causing multisystemic manifestations. She was treated conservatively. Amlodipine was discontinued, and oral ketone and bilastine were started. She had a complete recovery.